Opto-Electronic Investigation of Rubidium Based Fluoro-Perovskite for Low Birefringent Lens Materials - M. A. Iqbal; N. Erum (Scientific Inquiry and Review, 2017)
In this communication, systematic first principles calculation has been scrutinize to evaluate bonding nature, structural, electronic, and optical properties of RbHgF3. The findings are based on total energy calculations where Khon Sham (KS) equation is solved by means of density functional theory (FP-LAPW) method. Optimization of structural parameters is done with variety of approximations, which corroborates through comparison with available experimental data. Assessment of band profile through GGA plus Trans-Blaha modified Becke–Johnson (TB-mBJ) potential highlights underestimation of bandgap with traditional Generalized Gradient approximations. Specific contribution of particular states on electronic properties is investigated by means of total and partial density of states while contour maps of electron density are used to sightsee bonding character and it is evaluated that emphasized compound is (M-Γ) indirect bandgap material with mixed ionic and covalent bonding character. Additionally attention is paid to absorption and reflection spectra of RbHgF3fluoroperovskite by reconnoitering optical properties, which shows extensive absorption and reflection in high frequency regions. Expectantly, current study would benchmark various quantum mechanical effects, which must be taken into account to understand and utilize RbHgF3 in fabricating practical devices.